Examining the Effects of Ostracism and Overinclusion in the Eating Disorder Binge Spectrum: Evidence From a Controlled Cyberball Task. - Meneguzzo, Paolo; De Mico, Alberto; Collantoni, Enrico; Meregalli, Valentina; Tenconi, Elena; Favaro, Angela (European Eating Disorders Review, 2025)
Objective: Eating disorders (ED), including bulimia nervosa (BN) and binge eating disorder (BED), are characterised by dysfunctional eating behaviours and maladaptive emotional regulation tied to concerns about body image. This study investigates the emotional and cognitive impacts of social exclusion and overinclusion on individuals with ED using the Cyberball task, a computerised simulation of social interaction, to examine the role of early maladaptive schemas (EMS) in these responses. Method: The sample included 124 women: 34 with BN, 26 with BED, and 64 controls, assigned to either an ostracism or overinclusion condition. Emotional responses were measured using PANAS before and after the Cyberball task, and EMS were assessed via the Young Schema Questionnaire. Mediation models were applied to explore EMS effects on emotional responses. Results: Participants with ED showed unique emotional patterns compared to controls across both Cyberball conditions. In the overinclusion condition, controls experienced increased positive affect, whereas individuals with ED showed no significant change. During ostracism, ED participants reported reduced negative affect, suggesting complex reactions to social exclusion. EMS were found to mediate emotional responses, particularly in the overinclusion condition. Discussion: The findings underscore the distinct social‐cognitive and emotional effects of interpersonal interactions on individuals with BN and BED, emphasising the importance of addressing EMS and social cognition in treatment. Future research should focus on refining our understanding of social perception and emotional skills in ED populations, particularly within the bulimic spectrum. Summary: Emotional and cognitive shifts emerged during social interaction tasks.Individuals with binge‐spectrum felt less belonging and self‐esteem when overincluded.Emotional responses differed between clinical and control groups.Negative self‐beliefs explained mood changes after social interactions.Targeting self‐beliefs may improve emotional regulation in eating disorders.